Allergies in Orthodontics: From Causes to Management - Singh, Raj Kumar; Gupta, Nishant; Goyal, Varun; Singh, Gurkeerat; Chaudhari, Ankit (Orthodontic Journal of Nepal, 2019)
Concern about allergic reactions in orthodontic patients has been expressed regularly. Patients undergoing orthodontic treatment with fixed appliances are exposed to various biomaterials. Awareness of reactions that can occur with these dental materials is important to the orthodontist. The aim of this paper is to review the current literature on allergy in orthodontics and the implications of the allergic reaction in the management of patients during orthodontic treatment. Diagnosis and treatment should include a multidisciplinary team. In all instances, the patient’s well-being should guide treatment decisions, and general health not just oral health should be the goal.